Role of mTORC1 in mechanically induced increases in translation and skeletal muscle mass - Goodman, Craig A (Journal of applied physiology (1985), 2019)
Skeletal muscle mass is, in part, regulated by the rate of mRNA translation (i.e., protein synthesis). The conserved serine/threonine kinase, mTOR (the mammalian/mechanistic target of rapamycin), found in the multiprotein complex, mTOR complex 1 (mTORC1), is a major positive regulator of protein synthesis. The purpose of this review is to describe some of the critical steps in translation initiation, mTORC1 and its potential direct and indirect roles in regulating translation, and evidence that mTORC1 regulates protein synthesis and muscle mass, with a particular focus on basal conditions and the response to mechanical stimuli. Current evidence suggests that for acute contraction models of mechanical stimuli, there is an emerging pattern suggesting that there is an early increase in protein synthesis governed by a rapamycin-sensitive mTORC1-dependent mechanism, while at later poststimulation time points, the mechanism may change to a rapamycin-insensitive mTORC1-dependent or even an mTORC1-independent mechanism. Furthermore, evidence suggests that mTORC1 appears to be absolutely necessary for muscle fiber hypertrophy induced by chronic mechanical loading but may only play a partial role in the hypertrophy induced by more intermittent types of acute resistance exercise, with the possibility of mTORC1-independent mechanisms also playing a role. Despite the progress that has been made, many questions about the activation of mTORC1, and its downstream targets, remain to be answered. Further research will hopefully provide novel insights into the regulation of skeletal muscle mTORC1 that may eventually be translated into novel exercise programing and/or targeted pharmacological therapies aimed at preventing muscle wasting and/or increasing muscle mass.